1962
DOI: 10.1677/joe.0.0240159
|View full text |Cite
|
Sign up to set email alerts
|

A Study of the Roles of Adrenocortical Steroids and Glomerular Filtration Rate in the Mechanism of the Diurnal Rhythm of Water and Electrolyte Excretion

Abstract: 1. An investigation of the mechanism of diurnal excretory rhythms has been carried out on four healthy male subjects in whom the excretory rhythms were reversed by a 12 hr. shift of the activity-sleep and lightdark schedules.2. The diurnal rhythms of water, sodium, potassium, creatinine and ketogenic steroid excretion adapted to the reversal of routine at different rates.3. It is concluded, from the dissociation of these rhythms during the reversal phase, that the ketogenic steroids are not controlling either … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…In normal subjects, the morning rise in cortisol production coincides with the increase in electrolyte excretion but this does not mean that they are interdependent. Martel et al (1962) have shown that when normal subjects change their sleeping habits reversal of electrolyte excretion precedes by several days any change in cortisol production. Doe, Vennes & Flink (1960) found that cortisol given in doses of 5 mg every 3 hr throughout the day re-established a normal circadian rhythm of electrolyte excretion in patients with Addison's disease despite a constant excretion of cortisol metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In normal subjects, the morning rise in cortisol production coincides with the increase in electrolyte excretion but this does not mean that they are interdependent. Martel et al (1962) have shown that when normal subjects change their sleeping habits reversal of electrolyte excretion precedes by several days any change in cortisol production. Doe, Vennes & Flink (1960) found that cortisol given in doses of 5 mg every 3 hr throughout the day re-established a normal circadian rhythm of electrolyte excretion in patients with Addison's disease despite a constant excretion of cortisol metabolites.…”
Section: Discussionmentioning
confidence: 99%
“…In the second series of experiments (Martel et al 1962) urine was sampled every second day after phase reversal, and again every second day after return to normal time, and these data are also presented in Fig. 12. It appears that adaptation, and readaptation, of both potassium and sodium rhythms took about 6 days, but any individual differences are again obscured by the presentation of the mean of the four subjects involved.…”
Section: Urinary Rhythmsmentioning
confidence: 99%
“…Above, data of Sharp (1960), mean of six subjects; mean of four control days, third day after phase reversal, and mean of sixth, ninth and twelfth days after phase reversal. Below, data of Martel et al (1962), mean of four subjects; mean of four control days, then values every second day after phase reversal, and again after return to normal phase.…”
Section: Urinary Rhythmsmentioning
confidence: 99%
“…The mechanisms underlying the diurnal variations in the composi tion of urine are not yet known (2,7,17,20,22,23,30,31,35,38). However, the results of most previously reported studies and of this investigation reveal the similarity of the diurnal urinary excretory pat terns in subjects from various geographical locations living under different environmental conditions (2,8,16,17,35,38).…”
Section: Discussionmentioning
confidence: 54%
“…They are characterized by a simultaneous rise in the output of urine, sodium, chloride, potassium and bicarbonate in the morning hours, with a peak around noon, the excretion of each being lowest at night (2,7,20,33,35). The process of urinary acidifi cation is also known to display cyclic changes.…”
Section: Variation Nyctémcral De La Composition Du Sang Et De L'urinementioning
confidence: 99%